Desenvolvimento e validação de método para determinação voltamétrica de selênio em leite materno - Ramalho, Douglas Arruda (2015)
In this work was development a method for the determination of total selenium in mature breast milk using differential pulse cathodic stripping voltammetry (DPCSV) with hanging mercury drop electrode (HMDE). For sampling, healthy women and low-income residents were selected in Cuiaba, subject to normal deliveries, the collections were made in the period 20-40 days after childbirth. The samples were lyophilized, with the sensed to increase the shelf life thereof and pre-concentrates them, and a process carried out by wet digestion assisted by microwave. A first digestion step used the 23 factorial design evaluating the effect of factors: digestion cycles in the microwave, HCl concentration and volume ratio of digesting solution (HNO3: H2O2). The linear range of the method was established to 0.25 to 25.0 µg L-1 , and the instrumental limits of detection and quantification were 0.028 and 0.085 µg L-1 , respectively, values suitable for quantifying in real samples. The recovery results for a sample in three fortification levels ranged from 95.85% to 111.14%. There were not evaluated the errors associated with the values of the recovery percentages for lack of reproducibility in measurements. A second step for digestion of the sample, the composition of the digesting solution was measured, to obtain a mixture to produce high oxidizing power and low residual acidity, as well as the heating parameters with respect to temperature and time in the microwave digester. The composition of the digesting solution of 4.0 mL of HNO3 and 2.0 mL of H2O2 and water heating procedure, with heating ramp and three levels with temperatures of 140 ° C, 180 ° C and 200 °C, suppressing reduction step Se (VI) with HCl and heating conditions were employed and were more effective and reproducible XVIII mineralization of the sample. The percentage of recovery for Se the fortification level of 12.0 µg Kg-1 , was 86.12% with RSD of 7.21%, showing good accuracy considering the complexity of the matrix. And the Se concentration determined by an external standard sample of milk was 4.85 ± 0.31 µg Kg-1